PERENCANAAN PEMBANGUNAN DI INDONESIA PASCAORDE BARU: REFLEKSI TENTANG PENGUATAN PARTISIPASI MASYARAKAT - Fuady, Helmy (Masyarakat Indonesia, 2012)
The development planning during the New Order period has been criticized becauseit was centralistic, technocratic and lack of public participation. In the reformationera, many important changes have influenced the development planning system in Indonesia. The changes include changing role of the Bappenas (National Development Planning Agency), decentralization, direct presidential and local head elections, as well as the strengthening roles of the parliament. This paper analyses whether or not these changes open a wider space for public participation in the development policy-making. The discussion shows that public participation has not yet as expected by theory. The mechanism for public participation inthe development planning did not changemuch compared to the situation during the New Order era. Public participation has only fairly achieved and political elites are dominating the policy-making arena.